VALIDITY OF STARTING ANTICONVULSANT THERAPY AFTER FIRST CONVULSIVE SEIZURE IN CHILDREN - Ye. S. Fetisova; N. N. Maslova (Бюллетень сибирской медицины)
As a result of survey of 190 children with paroksyzmal conditions, there were revealed 14, whom antiepileptik therapy was prescribed after fist seizure. It was defined that such therapeutic tactics may be justified in patients with organik damage of the brain, focal neurological symptomatik in case of spontaneous emergence of the first seizure.